2017
DOI: 10.1016/j.jinf.2017.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Avian influenza A in poultry stalls of Lahore District, Pakistan in 2009–2010

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 5 publications
1
6
1
Order By: Relevance
“…As previously reported 15 , the overall virus prevalence of H9 virus was 10.0% (CI 95% : 5.61%–14.39%). The highest individual town-level prevalence was recorded in Ravi town (17.1%; CI 95% : 4.4%–29.8%), while the lowest prevalence was seen in Gulberg and Aziz Bhatti towns (2.8%; CI 95% : 2.7–8.4%) (Fig.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…As previously reported 15 , the overall virus prevalence of H9 virus was 10.0% (CI 95% : 5.61%–14.39%). The highest individual town-level prevalence was recorded in Ravi town (17.1%; CI 95% : 4.4%–29.8%), while the lowest prevalence was seen in Gulberg and Aziz Bhatti towns (2.8%; CI 95% : 2.7–8.4%) (Fig.…”
Section: Resultssupporting
confidence: 82%
“…As previously reported, the overall prevalence of H9 in LBRS in Lahore was 10% 15 , higher than the 2.5% prevalence reported from China 23 , but lower than the 16.5% prevalence reported in Bangladesh 5 . Differences in these prevalence estimates in various countries could reflect diverse risk factors e.g.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…An increased number and density of live poultry may increase virus circulation and increases the risk of infection, subsequently increasing the probability of virus dissemination and genetic reassortment. [53][54][55][56] Other studies have reported risk factors such as handling dead birds, butchering, area of farm, swimming or bathing in household ponds, having sick or dead poultry, age, vaccination of poultry, and exposure to ducks. 15,45,46 In experimental studies, influenza virus has been recovered from air samples during slaughter of asymptomatic H5N1…”
Section: Discussionmentioning
confidence: 99%